تجليات ظاهـــــــــــرة التطيـــر في شعــــــــر ابن الـــــرومي - بلحاج, عباس (جامعة الوادي - University of Eloued, 2016)
لأدب ظاهرة إنسانية سايرت حياة الإنسان وتطوراتها، حيث عبر عنها بمختلف الطرائق التي جاء بها الكثير من الأدباء كابن الرومي ، فأضحت نتيجة أدبية ظلت خالدة، كونها الدعامة الأساسية التي ارتكز عليها الناس لإدراك ما خفي عنهم وفهمه واكتشافه من أنفسهم وما حولهم، كما كانت هذه الأعمال في أمس الحاجة إلى ما يقدمها ويجدد دورها ومكانتها لأن الأدب يحيا ويزدهر إذا صار بؤرة اهتمام النقد. Abstract : Literature is a human phenomenon that took a place in man life in its different stages so he expressed it in many manners that come from writers AS IBN EL -ROUMI hence it would be an eternal Literature result that has been considered as the focus of people in understanding and discovering all that was hidden in their selves and around them. On the other side these works needed to be introduced to people for having its new role that Literature could have a new life and prosperity when critics focus on it.
مقال
Keywords: ، شعر بن الرومي، ظاهـــــــــــرة التطيـــر